PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Median Wilestari; Diana Bilah (AKRUAL : Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of variable Leverage, Corporate Size and Corporate Social Responsibility against Tax Aggressiveness sector listed in BEI 2016-2020 period. Th population in this study is mining companies listed in BEI 2016-2020 period totaling 18 companies. The sampling technique used was purposive sampling. Technical analysis of the data used is the logistic regression analysis with the help of SPSS 25 for windows. The results showed that leverage had a negative effect on tax aggressiveness, Corporate Size had a positive effect on tax aggressiveness and Corporate social responsibility had a positive effect on tax aggressiveness.